In vitro remineralization of enamel subsurface lesions and assessment of dentine tubule occlusion from NaF dentifrices with and without calcium - A R Prabhakar; A Jaiswal Manojkumar; N Basappa (Wolters Kluwer Medknow Publications, 2013)
Currently, fluoride is the most effective preventive treatment for remineralization of incipient carious lesions and dentinal hypersensitivity due to wasting disorders. The products containing fluoride, calcium and phosphate are also claim to remineralize early, non-cavitated enamel demineralization. The aim of this study was to investigate and compare the efficacy of two such products, Tooth Mousse and Clinpro tooth crème on remineralization and tubule occluding ability with 5000ppm fluoride-containing toothpaste. Materials and Methods :Thirty third molar teeth were placed in demineralizing solution for 5 days such that only a window of 1mm x 5mm was exposed to the environment to produce artificial caries-like lesions and randomly assigned to three groups: Group I, 5000ppm sodium fluoride; Group II, GC MI paste plus and Group III, Clinpro tooth crème. Axial longitudinal sections of 140-160 μm of each tooth which included the artificial carious lesion taken and were photographed under polarized light microscope. The demineralized areas were then quantified with a computerized imaging system. The experimental materials were applied onto the tooth sections as a topical coating and subjected to pH-cycling for 28 days. To evaluate tubule occlusion ability, thirty dentin specimens of 2mm thickness were obtained from cervical third of sound third molars. Specimens were ultrasonicated and etched with 6% citric acid for 2 minutes to simulate the hypersensitive dentin. Specimens were randomly divided into above mentioned three groups (n=10). The test agents were brushed over the specimens with an electric toothbrush, prepared and observed under Scanning Electron Microscope for calculation of the percentage of occluded tubules. Results: Group I showed a significantly greater percentage of remineralization than Group III and Group II. Comparison of the remineralization potential between group II and group III were not significant.In case of dentine hypersensitivity, Group I and group III showed greater percentage of tubule occlusion ability than Group II. Intergroup comparison of the tubule occlusion potential of group I and group III were not significant. Interpretation and Conclusion: Within the limitations of our study, sodium fluoride showed relatively greatest remineralizing and dentinal tubule occlusion property when compared with GC MI paste plus and Clinpro tooth crème.